Nontransferable Utility Bankruptcy Games - Arantza Estévez-Fernández; Peter Borm; M. Gloria Fiestras-Janeiro (Tinbergen Institute, 2014)
In this paper, we analyze bankruptcy problems with nontransferable utility (NTU) from a game theoretical perspective by redefining corresponding NTU-bankruptcy games in a tailor-made way. It is shown that NTU-bankruptcy games are both coalitional merge convex and ordinal convex. Generalizing the notions of core cover and compromise stability for transferable utility (TU) games to NTU-games, we also show that each NTU-bankruptcy game is compromise stable. Thus, NTU-bankruptcy games are shown to retain the two characterizing properties of TU-bankruptcy games: convexity and compromise stability. As a first example of a game theoretical NTU-bankruptcy rule, we analyze the NTU-adjusted proportional rule and show that this rule corresponds to the compromise value of NTU-bankruptcy games.
Keywords: C71; 330; NTU-bankruptcy problem; NTU-bankruptcy game; Coalitional merge convexity; Ordinal convexity; Compromise stability; Core cover; Adjusted proportional rule